Environmental, Social, and Economic Challenges in Lowland Rice Production - Connor, Melanie; Malabayabas, Arelene Julia; de Guia, Annalyn; Wehmeyer, Helena; Pame, Anny Ruth; Htwe, Nyo Me; Zhong, Xuhua; Fu, Youqiang; Liang, Kaiming; Pan, Junfeng; Hu, Xiangyu; Liu, Yanzhuo; et al. (Springer, 2023)
The CORIGAP project was implemented in six main rice granaries in South and Southeast Asia. The project introduced several country-specific sustainable best management practices, including nutrient management, pest management, water management, and several postharvest technologies, among other specific practices. This chapter introduces each country and its respective challenges to rice production. It outlines cultivation practices, historical developments, and their impacts on opportunities for the development of the rice sector. This is accompanied by specific case studies that highlight the adoption of specific technologies and practices. Case studies encompass the adoption of various best management practices in Myanmar and Thailand, especially postharvest technologies. Furthermore, the chapter highlights the outreach of “One Must Do, Five Reductions” in Vietnam, the development and implementation of the “Three Controls Technology” and alternate wetting and drying (AWD) practices in China, rodent pest management in Indonesia, and weed and water management in Sri Lanka. These case studies identified positive agronomic, social, and economic changes. The chapter concludes by harnessing the agricultural development strategies in each country with a synthesis of outcomes and impacts.